Temporal Trends in Overweight and Obesity, Physical Activity and Screen Time among Czech Adolescents from 2002 to 2014: A National Health Behaviour in School-Aged Children Study - Sigmund, Erik; Sigmundová, Dagmar; Badura, Petr; Kalman, Michal; Hamrik, Zdenek; Pavelka, Jan (International journal of environmental research and public health, 2015)
This study examines trends in overweight and obesity, physical activity (PA) and screen time (ST) among Czech adolescents over a recent 12-year study period. Nationally representative samples consisted of 19,940 adolescents (9760 boys and 10,180 girls) aged 10.5-16.5 years from the Czech Health Behaviour in School-aged Children (HBSC) questionnaire-based surveys conducted in 2002, 2006, 2010 and 2014. Trends in the prevalence of overweight/obesity, meeting the recommendations for moderate-to-vigorous PA (MVPA) (≥60 min per day of MVPA) and excessive ST (>2 h per day) were estimated using logistic regression. Significant increases (p < 0.001) in the prevalence of overweight/obesity between the years 2002 and 2014 were evident for both adolescent boys (18.3%(2002)-24.8%(2014)) and girls (8.3%(2002)-11.9%(2014)). Compared to 2002, in 2014 significant decreases (p < 0.001) in meeting MVPA recommendations were observed among boys (32.2%(2002)-25.6%(2014)) and girls (23.2%(2002)-19.2%(2014)). Moreover, in boys we observed significant increases (p < 0.001) in excessive ST on weekdays (75.1%(2002)-88.8%(2014)), as well as on weekends (78.3%(2002)-91.9%(2014)) between the years 2002 and 2014. Increases in overweight/obesity with concomitant decreases in PA provide evidence in support of the current and upcoming efforts of government and commercial organizations in implementing interventions aimed at reducing excessive body weight among Czech adolescents.
Keywords: Prevalence; school-aged children; Obesity; cvičení; Time Factors; mladiství; Česká republika; excess body weight; mužské pohlaví; prevalence; obesity; počítače; Overweight; Czech Republic; dítě; Child; logistické modely; HBSC study; ženské pohlaví; Humans; physical activity; Computers; computer (PC) use; časové faktory; obezita; nadváha; Logistic Models; Exercise; Female; Adolescent; television (TV) watching; lidé; Male